FRI0438 TREATMENT UTILISATION PATTERNS OF ADVANCED THERAPIES IN PSORIATIC ARTHRITIS. (June 2019) - Harrold, Leslie; Patel, Pankaj; Zueger, Patrick; O'brien, Jacqueline; Litman, Heather J.; Feng, Hua; Mclean, Robert
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory arthropathy typically associated with psoriasis. Little is known regarding the pattern of advanced therapy use, such as biologics and targeted synthetic disease-modifying antirheumatic drugs (tsDMARDs), and how the characteristics of patients with PsA initiating these therapies differ by line of therapy. Objectives: To characterise the prescribing frequency of medication classes and compare characteristics across line of therapy groups among patients with PsA who initiated a biologic/tsDMARD. Methods: This observational study included patients with PsA in the US Corrona PsA/SpA Registry who initiated a biologic/tsDMARD between 31 March 2013 and 31 October 2018. Patients were grouped by line of therapy at time of drug initiation: 1st, 2nd, 3rd, or 4th-or-higher. For each group, frequencies of medication classes were calculated, and proportions (categorical variables) and means with standard deviations (continuous variables) were determined for patient demographic, clinical and disease activity characteristics, patient-reported outcome measures, history of medication use, and concomitant medication use at the time of therapy initiation. Comparisons across groups were made with chi-square tests and one-way analysis of variance. Results: Data from 1516 initiators (396 (26%), 453 (30%), 333 (22%), 334 (22%) in the 1st, 2nd, 3rd, or 4th-or-higher line groups, respectively) were examined. Mean age was 53.1 years, mean time since PsA diagnosis was 8.1 years and mean time from PsA diagnosis to 1st line therapy initiation was 5.2 years. TNFi therapy was commonly initiated earlier, while initiation of the other classes as a proportion of total line-specific initiations increased in later lines of therapy (TNFi: 77%, 61%, 41%, and 30%; tsDMARDs: 16%, 18%, 19%, and 22%; IL-17: 4%, 12%, 25%, and 34%; non-TNFi/non-IL-17: 3%, 8%, 14%, and 14% for the 1st, 2nd, 3rd, and 4th-or-higher lines of therapy, respectively). Among all initiators, 72% had a history of methotrexate (MTX) use and 35% had concomitant MTX use at drug initiation. Most patients had moderate to high disease activity at therapy initiation based on the proportion of patients reporting minimal disease activity (20%) (Table ); 30% had enthesitis and 15% had dactylitis. Across therapy lines, statistically significant differences in minimal disease activity, HAQ, fatigue, pain and morning stiffness (P<0.05) were seen. Generally, scores were lower for those receiving 1st line therapy relative to the 4th-or-higher line group; fatigue scores ranged from 45.1 to 56.8, pain scores ranged from 46.6 to 58.2, and the percentage of patients with morning stiffness ≥30 minutes ranged from 72% to 80%. Conclusion: Patients with PsA who initiated biologic/tsDMARD therapies in a large, national US based registry frequently exhibited significant disease activity, as demonstrated by patient-reported outcome measures and validated disease activity measures. On average, disease activity was worse in later lines of therapy. Enthesitis and dactylitis were highly prevalent in this population. TNFi was the most common 1st line therapy while newer agents such as IL-17 inhibitors were most commonly initiated as 4th line therapy or higher. In light of the newly published guidelines, it appears that rheumatologists are treating in a manner aligned with the guidelines based on the characteristics of patients observed across the different lines of therapy. Acknowledgement: This study was sponsored by Corrona, LLC. Corrona is supported through contracted subscriptions with multiple pharmaceutical companies. The abstract was a collaborative effort between Corrona and AbbVie with financial support provided by AbbVie. Disclosure of Interests: Leslie Harrold Shareholder of: Corrona, Grant/research support from: Pfizer, Consultant for: AbbVie, BMS, and Genentech, Employee of: Corrona, Pankaj Patel Shareholder of: AbbVie, Employee of: AbbVie, Patrick Zueger Shareholder of: AbbVie, Employee of: AbbVie, Jacqueline O'Brien Employee of: Corrona, Heather J. Litman: None declared, Hua Feng Employee of: Corrona, Robert McLean: None declared